APLIKASI MATLAB DALAM MENGUKUR KEBULATAN HASIL INDENTASI UJI KEKERASAN BAGI KARYAWAN PT. SRI TERANG LINGGA PALEMBANG - Irawan Malik; Moch Yunus; Soegeng Witjahjo; Romli Romli (Aptekmas Jurnal Pengabdian pada Masyarakat, 2019)
Provision of spare parts for production equipment needs to be prepared with specifications, number of needs and correct time of availability, and especially for critical machining components that require correct and appropriate tactics so as not to disrupt its continuity of production. However, it is not a secret for a production department to make replacement parts that have the same mechanical properties through hardness testing of components that have failed. Through a computer program with an algorithm that is able to read a photo as a result of an indentation emphasis on hardness test, it can be known quickly a roundness diameter and calculate its hardness value which will be converted into one of the mechanical properties of a material so that a profile projector is not needed. Core of this implementation of our community service program is through an assignment scheme for employees of PT. Sri Trang Lingga Palembang, located on road TPA 2, RT. 26, RW. 29, Keramasan Subdistrict, Kertapati, Palembang City, South Sumatra, postal code 30149 is how to provide theoretical and experimental knowledge of the implementation of hardness tests on metal materials by emphasizing use of computer algorithms in reading photos of indentation hardness test results as an alternative to replacement use profile projector tool that is usually used for students of D-IV Mechanical Engineering Production and Maintenance (TMPP) Department of Mechanical Engineering Sriwijaya State Polytechnic to determine size of the indentation diameter emphasis from Brinnel hardness test.